2018
DOI: 10.1074/jbc.ra117.001698
|View full text |Cite
|
Sign up to set email alerts
|

A human-specific, truncated α7 nicotinic receptor subunit assembles with full-length α7 and forms functional receptors with different stoichiometries

Abstract: The cholinergic α7 nicotinic receptor gene, , encodes a subunit that forms the homopentameric α7 receptor, involved in learning and memory. In humans, exons 5-10 in are duplicated and fused to the genetic element, giving rise to the hybrid gene Its product, dupα7, is a truncated subunit lacking part of the N-terminal extracellular ligand-binding domain and is associated with neurological disorders, including schizophrenia, and immunomodulation. We combined dupα7 expression on mammalian cells with patch clamp r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 57 publications
4
33
0
Order By: Relevance
“…Lasala, et al also demonstrated that CHRFAM7A expression alters the assembly of the α7nAChR homopentamer in mammalian BOSC-23 kidney cells [16]. Utilizing a human kidney cell line, they showed that CHRFAM7A expression resulted in heteromeric receptors containing combinations of α7 and CHRFAM7A subunits.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lasala, et al also demonstrated that CHRFAM7A expression alters the assembly of the α7nAChR homopentamer in mammalian BOSC-23 kidney cells [16]. Utilizing a human kidney cell line, they showed that CHRFAM7A expression resulted in heteromeric receptors containing combinations of α7 and CHRFAM7A subunits.…”
Section: Discussionmentioning
confidence: 96%
“…Uniquely human CHRFAM7A is a partial duplication and rearrangement of the CHRNA7 gene that encodes the α7nAChR. Previous data suggests that CHRFAM7A expression may alter the structure of the α7nAChR [16]. CHRFAM7A expression is highly variable across individuals suggesting that α7nAChR function may be variable as well [9].…”
Section: Discussionmentioning
confidence: 99%
“…Allosteric activation of α7 through a transmembrane site has been shown for 4BP-TQS. However, the activity profile is strikingly different to that of ACh, which is not the case of Aβ (Gill et al, 2011; Lasala et al, 2018). Alternatively, Aβ may not occupy the five orthosteric agonist sites but may still be able to induce activation; the remaining sites, subsequently occupied by Carb, may favor activation and desensitization.…”
Section: Discussionmentioning
confidence: 99%
“…The open and closed time histograms obtained from idealization were fitted by the maximum interval likelihood (MIL) function in QuB (Qin et al, 1996, 1997), with a dead time of 0.1 ms. This analysis was performed by sequentially adding an open and/or closed state to a starting C ↔ O model in order to properly fit the corresponding histograms (Fabiani et al, 2018; Lasala et al, 2018). Final models contained five-six closed states and three-four open states for α7 in the presence of ACh plus PNU-120596, five-six closed states and three open states for α7 in the presence of ACh plus NS-1738, or three closed states and one-two open states for α7 in the presence of ACh and absence of PAMs.…”
Section: Methodsmentioning
confidence: 99%
“…The inverted gene is expressed at the RNA level [ 8 ], but protein prediction algorithms suggest that translation is unlikely due to Kozak fragment length [ 7 ]. CHRFAM7A gets incorporated into the α7 nAChR homopentamer based on gene dosage [ 9 , 10 ] and functions as a dominant negative modulator [ 5 , 6 ]. We previously showed that CHRFAM7A decreases α7 nAChR channel open probability and mitigates Aβ 1–42 uptake beyond physiological concentrations [11] .…”
Section: Introductionmentioning
confidence: 99%